Determinacion del patron heterotico de 30 lineas de maiz derivadas de la poblacion 43SR del CIMMYT - Terron, A.=700 1 Preciado, E.; Cordova, H.; Mickelso, H.; Lopez, R.
(En, Es)
ilus., 14 ref.
Keywords: ZEA MAYS; VIGOR HIBRIDO; HIBRIDACION; FITOMEJORAMIENTO; COSTA RICA